PROFILE OF PATIENTS WITH MULTIDRUG-RESISTANT PULMONARY TUBERCULOSIS AT MERAUKE REGIONAL GENERAL HOSPITAL, MERAUKE REGENCY, SOUTH PAPUA, JANUARY 2021 – DECEMBER 2024 - Luana N. Achmad; Jimmi M. P. Aritonang; Febtusia Puspitasari; Ganda Pariama (Journal of Innovation Research and Knowledge, 2026)
Pulmonary MDR-TB is tuberculosis that is resistant to first-line drugs, especially isoniazid and rifampicin, due to genetic mutations at drug target sites, so it requires combinations of drugs from Groups A and B, and if needed, Group C. This descriptive study used medical records of MDR-TB patients treated at Merauke Regional Hospital from January 2021 to December 2024 and was analyzed univariately with SPSS version 26. Most patients were 18–59 years old (90.6%), female (53.1%), and had a history of previous TB treatment (89.3%), with a small proportion experiencing treatment interruption and treatment failure. Comorbidities included diabetes mellitus (6.3%) and HIV (18.8%), and the mortality rate was relatively high at 40.6%.